Fatamorgana: recreational pop-up pavilion in royal theme / Muhammad Afiq Norazmi ... [et al.] - Norazmi, Muhammad Afiq; Haikal, Muhammad Adam; Azmi, Nur Zahra Nabilah; Husain, Fazidah Hanim (2024)
The pop-up pavilion, Fatamorgana, portrays the versatility and innovative potential of pop-up structures in recreational and practical applications, demonstrating user experience through timber modular structure. Fatamorgana reimagines the pop-up pavilion as a space for cultural rediscovery. Inspired by the royal theme of UiTM as stated in Wasiat Raja-raja Melayu, this biophilic design seamlessly integrates nature with interactive exhibitions to educate visitors about Malay Royal history. The architecture embodies the concept of "blessing" through its form, inspired by the Bunga Mawar, and its innovative use of light, wind, and timber. The modular timber structure promotes sustainability and celebrates the Malay Royal character, while the fabric ceiling acts as both functional louvre and evocative element, mimicking the sea's rhythm. This sustainable haven fosters a deeper appreciation for the environment and royal cultural heritage, catalyzing community engagement and a potential cornerstone for local tourism.